The Influence of External Locus of Control, Emotion Dysregulation, and Social Support on Academic Procrastination in Overseas Students - Rahmifanti R. Jacub; Agus Basuki (AL-ISHLAH: Jurnal Pendidikan, 2025)
Academic procrastination is a prevalent issue among international students, influenced by multiple psychological and social factors. This study investigates the relationships between academic self-efficacy, social support, emotion dysregulation, and academic procrastination, with academic self-efficacy also examined as a mediating and moderating variable. Data were collected from international students enrolled in universities. Structural Equation Modelling (SEM) was employed to analyze the interrelationships among the variables, focusing on both direct and indirect effects. Findings revealed that social support significantly and positively predicted academic self-efficacy, which in turn negatively influenced academic procrastination. Moreover, social support also directly reduced procrastination levels. External locus of control indirectly increased academic procrastination through lowered academic self-efficacy. However, emotion dysregulation showed no significant direct or indirect effect on academic procrastination. Academic self-efficacy served as a significant mediator between both social support and external locus of control in relation to procrastination. The results underscore the importance of perceived social support and academic self-efficacy in mitigating academic procrastination among international students. While emotional dysregulation was hypothesized to influence procrastination, its non-significant effect suggests that other factors may moderate this relationship in international student populations. These findings highlight the potential effectiveness of interventions aimed at strengthening academic self-efficacy and social support systems to reduce procrastination behaviors in this group.